Aquatic plant surface as a niche for methanotrophs - Yoshida, Naoko; Iguchi, Hiroyuki; Yurimoto, Hiroya; Murakami, Akio; Sakai, Yasuyoshi (Frontiers in Microbiology, 2014)
This study investigated the potential local CH4 sink in various plant parts as a boundary environment of CH4 emission and consumption. By comparing CH4 consumption activities in cultures inoculated with parts from 39 plant species, we observed significantly higher consumption of CH4 associated with aquatic plants than other emergent plant parts such as woody plant leaves, macrophytic marine algae, and sea grass. In situ activity of CH4 consumption by methanotrophs associated with different species of aquatic plants was in the range of 3.7 – 37 μmol⋅h-1⋅g-1 dry weight, which was ca 5.7-370 fold higher than epiphytic CH4 consumption in submerged parts of emergent plants. The qPCR-estimated copy numbers of the particulate methane monooxygenase-encoding gene pmoA were variable among the aquatic plants and ranged in the order of 105 to 107 copies⋅g-1 dry weight, which correlated with the observed CH4 consumption activities. Phylogenetic identification of methanotrophs on aquatic plants based on the pmoA sequence analysis revealed a predominance of diverse gammaproteobacterial type-I methanotrophs, including a phylotype of a possible plant-associated methanotroph with the closest identity (86-89%) to Methylocaldum gracile.